A Biomimetic Drosera Capensis with Adaptive Decision‐Predation Behavior Based on Multifunctional Sensing and Fast Actuating Capability. (3rd December 2021) - Qiu, Ye; Wang, Chengjun; Lu, Xiaoyan; Wu, Huaping; Ma, Xiaolong; Hu, Jiahui; Qi, Hangcheng; Tian, Ye; Zhang, Zheng; Bao, Guanjun; Chai, Hao; Song, Jizhou; et al.
Abstract: The sophistication, adaptability, and complexity of biological systems have provided enormous inspiration and have been a continuous source of numerous innovations. Soft living organisms like drosera capensis have amazing predatory behavior that can capture prey of ideal size, enabling them to interact with environmental stimuli efficiently. Mimicking such natural intelligence in artificial systems with systematical functions of multiple information perception, neuronal transmission, and adaptive motility remains a grand challenge. Here, a biomimetic drosera capensis is reported that is capable of multifunctional self‐sensing, automatic regulation, and adaptive actuation in response to diverse stimuli with intelligent predation capability in an entirely closed‐loop fashion. The functional system heterogeneously integrates the thermal‐responsive soft actuator as the muscle‐like motor and flexible tactile, strain, and piezoelectric multimodal sensors as somatosensory receptors. With the synergistic effect of multifunctional sensing and fast actuating schemes, the artificial drosera capensis deconvolutes multiple characteristics of the catching process (e.g., strain rate, magnitude, and direction) and thus holds impressive predatory behavior for ideal‐sized prey. This electronically innervated artificial drosera capensis with multimodal sensing and self‐regulated actuating capability through the closed‐loop control of sensing and actuating system paves the way for the development of adaptive soft robots. Abstract : A biomimetic drosera capensis that is capable of multifunctional self‐sensing, automatic regulation, and adaptive actuation in response to various stimuli with intelligent predatory behavior in an entirely closed‐loop fashion is reported. With the synergistic effect of multifunctional sensing and fast actuating schemes, this electronically innervated artificial system with self‐regulated capability paves the way for the development of adaptive soft robotics.